Peripheral target choice by homologous neurons during embryogenesis of the medicinal leech. II. Innervation of ectopic reproductive tissue by nonreproductive Retzius cells - Loer, CM (J Neurosci, 1989)
Most Retzius (Rz) cells innervate the body wall of their own and adjacent segments, whereas Rz cells in segments 5 and 6 [Rz (5,6)] innervate the reproductive tissue, which is found only in those segments. Results from the preceding paper (Loer and Kristan, 1989a) showed that Rz (5,6) and standard Rz cells do not normally compete for their respective peripheral targets. These experiments did not, however, distinguish between 2 other possible mechanisms of target selection: intrinsic differences in target preference or differences in the timing of target contact. In order to separate these possibilities experimentally, we transplanted reproductive primordia to standard segments. We found that standard Rz cells were capable of densely innervating ectopic reproductive tissue, provided the target was transplanted at an appropriate time and location. Furthermore, after some processes of standard Rz cells contacted ectopic reproductive tissue, the rest of the cell's processes showed their growth in a way reminiscent of Rz (5,6) processes. These results strongly suggest that Rz (5,6) innervate reproductive tissue at least partly because their processes contact this target during a period that is optimal for them to associate with the target, or when the reproductive tissue is most attractive to Rz processes, or both.